Pelatihan Pembuatan Media Pembel PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS ICT SEBAGAI PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU SMK: PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS ICT SEBAGAI PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU SMK - Nagari, Primasa Minerva; Nuraini, Umi; Nuris, Dudung Ma'ruf (Universitas Muhammadiyah Malang, 2022)
The development of information and communication technology (ICT) requires a teacher to be able to understand and apply technology in the learning process in the classroom as a form of increasing pedagogic competence. There are various forms of ICT that can be integrated in the process of improving pedagogic abilities. This is done to face the digital era. By understanding the integration of ICT, it can be in the form of developing ICT-based learning media to improve the pedadoic competence of teachers. This training aims to assist teachers in developing ICT-based learning media so that they can also increase pedagogic competence. The method of community service activities is training at SMK Negeri 1 Rejotangan, where teachers are given material about ICT-based learning media and continued with direct practice. The training explained the importance of developing ICT-based learning media to teachers to provide enlightenment for students on the material presented in class and the practice of using applications that support the creation of learning media. From this training, teachers became very interested in ICT-based media as a medium for their learning. It is hoped that further training can use more diverse applications for ICT-based learning media training.